DINAMIKA NILAI TUKAR RUPIAH TERHADAP US DOLLAR: METODE MONETARY APPROACH - Maulida Fatmawati; Rr Retno Sugiharti (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The exchange rate is used as a tool to measure the economic condition of a country. This study aims to analyze the effect of the value of oil and gas imports, the money supply, and the BI Rate on the Rupiah exchange rate. This analysis uses a cointegration equation with an error correction model (ECM) approach, this study will analyze the relationship between the independent variable and the dependent variable in the long and short term. The estimation results from the cointegration equation show that in the long run the variable value of oil and gas imports, and the BI Rate have a significant effect on the rupiah exchange rate. The money supply (M2) in the long and short term has a significant effect on the rupiah exchange rate. Meanwhile, inflation has no effect on the rupiah exchange rate, both in the long and short term.